2007
DOI: 10.1111/j.1439-0310.2006.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Predictors of Range Areas and Use of Burrow Systems in the Diurnal Rodent, Octodon degus

Abstract: Variation in animal space use patterns may be linked to numerous ecological factors affecting survival and reproduction. We examined the relationship between ecology and above‐ and below‐ground components of space use by Octodon degus, a semi‐fossorial rodent in Chile. We monitored the daytime minimum convex polygon and adaptive kernel range areas of 26 individuals and determined the number of burrow systems used by degus during night‐time radiotelemetry and trapping of burrow systems on two study grids at Rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 62 publications
(152 reference statements)
1
54
1
Order By: Relevance
“…Annuals are short-lived, protein-rich plants, which are thought to be a critical resource for breeding in striped mice (Schradin & Pillay 2006). Spatial distribution of small mammals is often associated with dense cover (Asher et al 2004;Hayes et al 2007), probably because predation risk influences foraging activity (Kotler 1984;Anderson 1986;Brown et al 1988). We found that home ranges with little cover were larger, possibly because striped mice avoided areas without cover for foraging.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Annuals are short-lived, protein-rich plants, which are thought to be a critical resource for breeding in striped mice (Schradin & Pillay 2006). Spatial distribution of small mammals is often associated with dense cover (Asher et al 2004;Hayes et al 2007), probably because predation risk influences foraging activity (Kotler 1984;Anderson 1986;Brown et al 1988). We found that home ranges with little cover were larger, possibly because striped mice avoided areas without cover for foraging.…”
Section: Discussionmentioning
confidence: 67%
“…Intraspecific variation in home range size may be caused by many different factors, such as sex (e.g. Mikesic & Drickamer 1992;Asher et al 2004;Begg et al 2005), age (Mikesic & Drickamer 1992), reproductive effort (Tufto et al 1996;Saïd et al 2005), availability of nesting sites and cover (Tufto et al 1996;Getz et al 2005;Hayes et al 2007) and food availability (Taitt & Krebs 1981;Ims 1987;Tufto et al 1996;Jonsson et al 2002;Saïd et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Central place foragers are most likely to be found closer to the central Cowan 1987), construct burrow systems with .1 entrance, which may result in a clustered pattern. For these herbivores, the increased number of burrow openings is considered to decrease their risk of predation (Hayes et al 2007). Additionally, there is evidence that clustered resource patterns may be advantageous, allowing higher individual densities and perhaps aiding population persistence (Doncaster 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This observation agrees with other studies of pygmy rabbits that found increasing sagebrush cover leads to an increased probability of pygmy rabbit occurrence (e.g., Green and Flinders 1980b, Simons and Laundré 2004, Larrucea and Brussard 2008. Overhead vegetative cover was also positively correlated with placement of burrows by degus, and is thought to reduce their risk of predation (Hayes et al 2007). However, pygmy rabbits feed on big sagebrush, especially in winter (Green and Flinders 1980b), and sagebrush is the dominant overstory plant in our system (T. L. Wilson, unpublished data).…”
Section: Discussionmentioning
confidence: 99%